Culture and the Question of Rights : Forests, Coasts, and Seas in Southeast Asia - Zerner, Charles (Book collections on Project MUSE., 2003)
A collection of ethnographic studies into the nature of power, language, and cultural politics within the context of Southeast Asian environments.